2016
DOI: 10.1186/s13065-016-0217-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of acyl oleanolic acid-uracil conjugates and their anti-tumor activity

Abstract: BackgroundOleanolic acid, which can be isolated from many foods and medicinal plants, has been reported to possess diverse biological activities. It has been found that the acylation of the hydroxyl groups of the A-ring in the triterpene skeleton of oleanolic acid could be favorable for biological activities. The pyrimidinyl group has been constructed in many new compounds in various anti-tumor studies.ResultsFive acyl oleanolic acid-uracil conjugates were synthesized. Most of the IC50 values of these conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Several compounds in fraction B, such as rengyolone [ 22 ], licochalcone A [ 23 ], sugiol [ 24 , 25 ], and spinasterol [ 26 ], have been known to have activity against cancer cells. For fraction E, thymine [ 27 ], aschantin [ 28 ], lirioresinol B dimethyl ether [ 29 ], and others have potency as anticancer, as well.…”
Section: Resultsmentioning
confidence: 99%
“…Several compounds in fraction B, such as rengyolone [ 22 ], licochalcone A [ 23 ], sugiol [ 24 , 25 ], and spinasterol [ 26 ], have been known to have activity against cancer cells. For fraction E, thymine [ 27 ], aschantin [ 28 ], lirioresinol B dimethyl ether [ 29 ], and others have potency as anticancer, as well.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, unlike other compounds, compound 71c was found to be the least cytotoxic to healthy liver cell line (HL-7702). Further cell cycle analysis depicted that compound 71c could trigger apoptosis by activating caspase-3/9 and arrest the G1 phase of HEP-G2 cells (Mo et al, 2016).…”
Section: Uracil-oleanolic Acid Hybridmentioning
confidence: 99%
“…SAR studies of oleanolic acid showed that structural modification at C-3 and C-28 improves cytotoxic properties against prostate cancer (PC-3), lung cancer (A549), and breast cancer (MCF-7) cell lines (Hao et al, 2013). Being inspired by the evidence, Mo et al (2016) synthesized the conjugates of Acyl-oleanolic acid and Uracil. Synthetic pathway starts with the treatment of oleanolic acid (69) (1 equiv) with anhydride (1.5 equiv) and DMAP (0.1 equiv) in anhydrous CH 2 Cl 2 /pyridine at room temperature to yield 3-O-acyl derivatives (70a-c).…”
Section: Uracil-oleanolic Acid Hybridmentioning
confidence: 99%
“…Moreover, impairment of melanoma mitochondrial function was observed, in contrast to the effect observed in the non-tumor keratinocytes cell line [ 57 ]. High selectivity of conjugates with uracil, particularly in hepatoma HepG2 cells, in the induction of apoptosis (triggering caspase-3/9 activity), was claimed [ 58 ].…”
Section: Conjugation Of Synthetic Oa Derivatives May Enhance Their Anti-cancer Potentialmentioning
confidence: 99%